Enhanced electrophoretic DNA separation in photonic crystal fiber - Sun, Yi (2012)
Joule heating generated by the electrical current in capillary electrophoresis leads to a temperature gradient along the separation channel and consequently affects the separation quality. We describe a method of reducing the Joule heating effect by incorporating photonic crystal fiber into a micro capillary electrophoresis chip. The photonic crystal fiber consists of a bundle of extremely narrow hollow channels, which ideally work as separation columns. Electrophoretic separation of DNA fragments was simultaneously but independently carried out in 54 narrow capillaries with a diameter of 3.7 μm each. The capillary bundle offers more efficient heat dissipation owing to the high surface-to-volume ratio. Under the same electrical field strength, notable improvement in resolution was obtained in the capillary bundle chip.